2009
DOI: 10.1542/peds.2008-2004
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cerebral Pressure Passivity Is Associated With Prematurity-Related Intracranial Hemorrhage

Abstract: OBJECTIVES Cerebral pressure passivity is common in sick premature infants and may predispose to germinal matrix/intraventricular hemorrhage (GM/IVH), a lesion with potentially serious consequences. We studied the association between the magnitude of cerebral pressure passivity and GM/IVH. PATIENTS AND METHODS We enrolled infants <32 weeks’ gestational age with indwelling mean arterial pressure (MAP) monitoring and excluded infants with known congenital syndromes or antenatal brain injury. We recorded contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 50 publications
(51 reference statements)
3
116
1
4
Order By: Relevance
“…Since the start of this clinical study, methodological reviews have indicated that it is better to use gain rather than coherence as a measure of CA, and only in measurements with significant coherence (1,32). Approximately half of our study population was lost in the application of this methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the start of this clinical study, methodological reviews have indicated that it is better to use gain rather than coherence as a measure of CA, and only in measurements with significant coherence (1,32). Approximately half of our study population was lost in the application of this methodology.…”
Section: Discussionmentioning
confidence: 99%
“…We used Monte Carlo simulations to determine this cutoff (≥0.47 in VLF and ≥0.45 in LF (39)). In the subgroup of infants with significant coherence (i.e., impaired CA), gain was used to estimate the magnitude of impairment in CA (1,32).…”
Section: Calculation Of Nirs-derived Measures Of Ca (Coherence and Gain)mentioning
confidence: 99%
“…Associations between the development of cerebral pathology and impairment of cerebrovascular autoregulation have been reported. Tsuji et al and O'Leary et al reported that dynamic autoregulation impairment was associated with an increased risk of developing GMH/IVH or PVL [6,41]. Alderliesten et al found a statistically significant correlation between regional cerebral oxygen saturation (rSO 2 ) and ABP, suggestive of impaired autoregulation, before the development of mild-to-moderate IVH.…”
Section: Clinical Factorsmentioning
confidence: 99%
“…Others focus on the techniques and hardly give any information on the infants included, which may hamper interpretation of data presented. Out of the 25 articles studied, 14 mention PaCO 2 as a possible confounder, of which 3 actually measured PaCO 2 and assessed the relationship between PaCO 2 and outcome [34,41,42] and 2 assessed the influence of PaCO 2 on cerebrovascular autoregulatory measures [29,56]. None found any relation between PaCO 2 , outcome, and autoregulation status.…”
Section: Clinical Informationmentioning
confidence: 99%
“…That is, from descriptions of total cerebral blood flow responses to changes in BP over a minute or so in time, to the descriptions of the nearly continuous fluctuations in cerebral blood flow in response to nearly continuous changes in BP. Reports by Tsuji et al 7 and O'Leary et al 8 use frequency domain analysis to demonstrate that preterm infants can autoregulate cerebral blood flow, but that periods of pressure passivity are common and predispose to IVH.…”
mentioning
confidence: 99%